Diseño de un plan de seguridad y salud ocupacional según la ley 29783, su reglamento D.S. 005 - 2012 – TR y sus modificatorias en la empresa fortaleza S.R.L en la ciudad de talara, 2016 - Moreno Pérez, Gerson Jair (2018)
Occupational Health and Safety has the purpose of creating the conditions for the worker to carry out their work efficiently and without risks, avoiding events and damages that may affect their health and integrity, the entity's assets and the environment, and thus promoting the raising of the quality of life of the worker, his family and social stability. The present research work based on the "DESIGN OF AN OCCUPATIONAL HEALTH AND SAFETY PLAN ACCORDING TO LAW 29783, ITS REGULATIONS D.S. 005 - 2012 - TR AND ITS MODIFICATORIES AT THE COMPANY FORTALEZA SRL IN THE CITY OF TALARA, 2016 "; Its main objective is to minimize the dangers and risks to which employees are exposed every day. The company has as main services are industrial assembly, industrial paints, heavy machinery rental and construction and repair of civil works. For the study, methods of data collection have been used through surveys, interviews and field visits to subsequently record it in the IPERC matrix, where it is verified which are the most critical hazards and risks and finally find the optimal control measures. The diagnosis of the current situation of the company was made, with the purpose of verifying the percentage of compliance with the guidelines according to Law N ° 29783 and regulation DS-005-2012-TR. In this chapter it was possible to show that there was no record of accidents and work incidents although they had occurred recurrently. Subsequently, the proposal for the design of the Occupational Health and Safety Plan is defined according to law 29873, which applies to all workers involved in the processes and activities developed by the company FORTALEZA S.R.L; As a result of the theoretical application of new administrative, management and engineering controls and the modernization of collective and individual protection equipment, a total reduction of intolerable risks was obtained, from 19% to 0%, significant risks, 34% to 17%. %, transferring this percentage reduction to moderate, tolerable and trivial risks (Moderate 38%, Tolerable 31%, Trivial 14%). Finally, the economic feasibility of the present project was determined through the results of the profitability indexes such as the net present value (NPV: 55,007.09), the internal rate of return (IRR: 18.73%) and the B / C which is of 1.97.